Can AI Predict Clinical Trial Outcomes? - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2020)
Clinical trials are the cornerstone of modern medicine, serving as the final and most critical step in the long and arduous journey of drug development. Howe...
Keywords: Drug Discovery and Pharmaceutical AI; Predict; Clinical; Trial; Artificial Intelligence; Machine Learning; Deep Learning